1998
DOI: 10.1089/neu.1998.15.509
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Brain Tissue Oxygen Tension to Microdialysis-Based Measures of Cerebral Ischemia in Fatally Head-Injured Humans

Abstract: This study investigated the relationship between brain tissue oxygen tension (PbtO2) and cerebral microdialysate concentrations of several compounds in five patients with refractory intracranial hypertension after severe head injury. The following substances were assayed: lactate and glucose; the excitatory amino acids glutamate and aspartate; and the cations potassium, calcium, and magnesium. Glucose concentrations did not correlate with PbtO2, but lactate increased as PbtO2 decreased. The lactate/glucose rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
6

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(63 citation statements)
references
References 30 publications
1
53
0
6
Order By: Relevance
“…Studies have shown that local brain tissue PO 2 levels are significantly correlated with ischemia and outcome. 54,55 Hyperbaric O 2 therapy clearly leads to Graph showing microdialysate L/P ratio in "uninjured" brain with posttreatment/pretreatment ratio means. A value > 1 indicates the posttreatment value is greater than the pretreatment value, and a value < 1 indicates the posttreatment value is less than the pretreatment value.…”
Section: Mechanism Of Hbomentioning
confidence: 99%
“…Studies have shown that local brain tissue PO 2 levels are significantly correlated with ischemia and outcome. 54,55 Hyperbaric O 2 therapy clearly leads to Graph showing microdialysate L/P ratio in "uninjured" brain with posttreatment/pretreatment ratio means. A value > 1 indicates the posttreatment value is greater than the pretreatment value, and a value < 1 indicates the posttreatment value is less than the pretreatment value.…”
Section: Mechanism Of Hbomentioning
confidence: 99%
“…5 In traumatic brain injury, episodes of low cerebral oxygenation are also associated with poor outcome. 6,7 Brain tissue oxygen tension (P b O 2 ) reflects the availability of oxygen for oxidative energy production and represents the balance between oxygen supply and demand. Ischemic thresholds for P b O 2 have been described, ranging from 1.1 kPa to 3.3 kPa.…”
mentioning
confidence: 99%
“…For instance, in cases of cerebral ischemia, the lacate/pyruvate ratio increases markedly, whereas the glucose level declines to near zero. These findings have been shown to correlate with SjVO 2 and PbrO 2 measurements, as well as the oxygen extraction fraction as measured by PET (Robertson et al 1995;Valadka et al 1998;Hutchinson et al 2002). When used in conjunction with CPP and ICP monitoring, microdialysis may have a role in early detection of focal (as opposed to global) pathological processes, such as vasospasm or expanding contusions (Valadka & Robertson 2007;Hillered, Vespa, & Hovda 2005).…”
Section: Microdialysismentioning
confidence: 89%